Review of Chinese species of the genus Nakaharanus Ishihara (Hemiptera: Cicadellidae: Deltocephalinae), with description of a new species - Wei, Xingtao; Xing, Jichun (Zootaxa, 2019)
The Chinese species of the genus Nakaharanus Ishihara are reviewed, and a new species Nakaharanus lii sp. nov. is described and illustrated. Nakaharanus sagittarius Kwon & Lee, 1979 is recorded from China for the first time. Two keys based on the male genitalia and female seventh sternum are given to distinguish Chinese species of this genus. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).